2022
DOI: 10.1073/pnas.2107189119
|View full text |Cite
|
Sign up to set email alerts
|

FAF1 blocks ferroptosis by inhibiting peroxidation of polyunsaturated fatty acids

Abstract: Significance The current study reveals the functions of FAF1 in protecting cells from ferroptosis, a novel cell death pathway triggered by PUFA peroxidation. In the absence of FAF1, cultured cells and mice are extremely sensitive to ferroptosis when exposed to physiological levels of PUFAs. Mechanistically, FAF1 sequesters PUFAs into the hydrophobic core of a global structure that limits their access to positively charged Fe 2+ , which catalyzes the peroxidation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Excessive oxidation of phospholipids in polyunsaturated fatty acids (PUFAs) also contributes to cell ferroptosis [ 34 ]. PUFAs are an essential component of the phospholipid bilayer of the cell membrane and play an indispensable role in maintaining cell membrane fluidity [ 35 ].…”
Section: New Approaches To Metal Ions-induced Cell Death and Their An...mentioning
confidence: 99%
“…Excessive oxidation of phospholipids in polyunsaturated fatty acids (PUFAs) also contributes to cell ferroptosis [ 34 ]. PUFAs are an essential component of the phospholipid bilayer of the cell membrane and play an indispensable role in maintaining cell membrane fluidity [ 35 ].…”
Section: New Approaches To Metal Ions-induced Cell Death and Their An...mentioning
confidence: 99%
“…[10] In the presence of unsaturated FAs, assembly of the FAF1-FFA complex not only enables cell proliferation by stabilization of β-catenin [10] but also prevents PUFA peroxidation to protect cells from ferroptosis. [5] Cancer genomic studies have revealed that FAF1 is frequently inactivated in glioblastoma and hereditary colorectal cancer, presumably because of their growth advantage through stabilization of β-catenin. [27,28] It will be interesting to determine whether these cancers are vulnerable to PUFA-induced ferroptosis.…”
Section: Cancer Developmentmentioning
confidence: 99%
“…However, direct visualization of the FAF1‐FFA complex in cells remains challenging as this membraneless organelle is destroyed by conventional cell fixation and permeabilization procedures for fluorescent microscopy and EM analysis that are optimized to preserve structures surrounded by membranes. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations